Cognitive Offloading: Can ubimus technologies affect our musicality? - Costalonga, Leandro; Pimenta, Marcelo (Anais do Simpósio Brasileiro de Computação Musical (SBCM), 2019)
An interaction design that lean towards musical traits based on and constrained by our cognitive and biological system could, not only provide a better user experience, but also minimize collateral effects of excessive use of such technology to make music. This paper presents and discuss innate abilities involved in musical activities that - in the authors´ viewpoint - could be considered in design guidelines to computer music technologies, especially those related to ubimus.